Rare earth elements recovery from end-of-life NdFeB magnets towards new applications using design of experiments for leaching process - Ana Paula Silva; Óscar Barros; Pier Parpot; Isabel C. Neves; Teresa Tavares; José Pinheiro-Torres; Bruna Silva (Minerals Engineering, 2026)

Collaborative studies on in vitro digestibility of dietary proteins based on the INFOGEST Quant protocol: toward international standardization - Lotti Egger; Ana Blanco-Doval; Cédric Brügger; Raquel Sousa; Lychou Abbühl; Marta Santos Hernández; Beatriz Miralles; Cristina Gómez-Marin; Adam Macierzanka; Patrycja Szumała; Ilona E. Kłosowska-Chomiczewska; Ana Isabel Mulet-Cabero; et al. (Food Research International, 2026)

Corrigendum to “Production of sustainable aviation fuel precursors using the oleaginous yeast Rhodotorula toruloides PYCC 5615 cultivated on eucalyptus bark hydrolysate” [Biomass Bioenergy 197 (2025) 107790] - Teresa Lopes da Silva; Francisca Dutra; Susana Marques; Miguel Gomes; Paula Costa; Filipe Paradela; Frederico Castelo Ferreira; Nuno Torres Faria; Paula Mugica; Helena M. Pinheiro; Isabel Sá-Correia; Francisco Gírio (Biomass and Bioenergy, 2026)

From waste to circularity: the potential of different treatments of poultry manure and forestry residues in a hot-spot production region in Portugal - Ana d’Espiney; Bengt Verworner; Helena M. Pinheiro; Isabel P. Marques; Katja Oehmichen; Nils Engler; Stefan Majer; Walter Stinner; Daniela Thrän (The International Journal of Life Cycle Assessment, 2026)
Purpose The management of biogenic residues in a way that extends the lifetime of carbon within the systems is a focus of the present work. Different waste management systems are assessed in terms of GHG emissions and removals, aiming to identify that with the lowest impact on climate change. Methods A life cycle comparative analysis is performed, assessing the mitigation of the impact on climate change of the current waste management system (A) of the top two residues of a Portuguese region – composting of poultry manure and open air burning of forestry residues – considering two bioenergy solutions: biochemical conversion of poultry manure and thermochemical conversion of wood residues (B); biochemical conversion for both residues together (C), implying fungal pre-treatment of the wood residues, which adds a food product to the supply chain. Data were retrieved from literature and from authors’ experimental work. Assumptions underlying the methodological framework (e.g., cut offs inherent to comparative assertions) are discussed. A sensitivity analysis covers uncertainties underpinning bioenergy systems assessments (e.g., unperfect substitution and rebound effect phenomena). Results and discussion The highest impact on climate change is observed with system A, greenhouse gas (GHG) emissions 2 to 3 times higher than those of the other two systems. System A also performs poorly in conserving the biomass, e.g., forestry residues burning results in carbon being directly released to the atmosphere with no valuable intermediate use. In the base scenario, system B results in the lowest GHG emissions of the three systems, producing biochar, which contributes to carbon sequestering, and biodiesel. Nevertheless, system C can result in the lowest GHG emissions, in a scenario considering unperfect substitution with renewable sources being selected to match the biodiesel supply of system B. Conclusions System A is least preferable among the three options. Between systems B and C, ranking depends on whether unperfect substitution is considered. System B performs better in all scenarios, except with unperfect substitution, where system C outranks B. Moreover, system C achieves a higher yield of digestate, a product providing other ecosystem services. Thus, in future research, the inclusion of other impact categories in LCA can reveal a better overall environmental performance for system C.

ProAKAP4 as a protein marker of sperm quality: Insights from frozen-thawed ejaculated and epididymal sperm - Myrian Megumy Tsunokawa Hidalgo; Ana Beatriz Marques de Almeida; Leticia Amanda dos Santos Silva; Vinicius Wagner Silva; Julia Rodrigues Greghi; Natália Ribeiro Sambatti; Luiz Guilherme Corsi Trautwein; Rodrigo Yudi Palhaci Marubayashi; João Carlos Pinheiro Ferreira; Maria Isabel Mello Martins (Theriogenology, 2026)

In loving memory of Deolinda Flores (1958–2025) - Manuela Marques; Isabel Suárez-Ruiz; Lopo Vasconcelos; Henrique Pinheiro; João Graciano Mendonça Filho (International Journal of Coal Geology, 2026)

Economic benchmarking of assisted pollination methods for kiwifruit flowers: Assessment of cost-effectiveness of robotic solution - Isabel Pinheiro; Pedro Moura; Leandro Rodrigues; Abílio Pereira Pacheco; Jorge Teixeira; António Valente; Mário Cunha; Filipe Neves dos Santos (Agricultural Systems, 2026)

Overlap evidence in fish microhabitat use in low-order rivers affected by small hydropower plants - Renan Leite; Isabel Boavida; Maria J. Costa; Francisco Godinho; Antonio N. Pinheiro; José Maria Santos (Ecohydrology & Hydrobiology, 2025)

Laying the Foundation: How Substrate Choice Influences Kelp Reforestation Success - Tomás F. Pinheiro; Sílvia Chemello; Isabel Sousa-Pinto; Tânia R. Pereira (Journal of Marine Science and Engineering, 2025)
Over recent decades, widespread declines of kelp forests have been reported along the European coast, prompting the need for effective and scalable restoration strategies. The green gravel technique, in which kelp gametophytes are seeded onto small rocks and cultivated in the lab before being outplanted, has shown promising results. In this study, we tested the effects of four commonly available substrates—granite, limestone, quartz, and schist—on the early development of Laminaria ochroleuca recruits under optimal laboratory conditions. All substrates supported gametophyte adhesion and sporophyte development. By week 6, quartz promoted the greatest recruit length (1.25 ± 0.16 mm), with quartz and limestone (1.54 ± 0.17 and 1.58 ± 0.14 mm, respectively) showing the best overall performance by week 7. Final recruit densities were similar across substrates, indicating multiple materials can support early development. Quartz and limestone showed both biological effectiveness and practical advantages, with limestone emerging as the most cost-effective option. Substrate selection should consider not only biological performance but also economic and logistical factors. These findings contribute to refining green gravel protocols and improving the feasibility of large-scale kelp forest restoration, although field validation is necessary to assess long-term outcomes under natural conditions.

Production of sustainable aviation fuel precursors using the oleaginous yeast Rhodotorula toruloides PYCC 5615 cultivated on eucalyptus bark hydrolysate - Teresa Lopes da Silva; Francisca Dutra; Susana Marques; Miguel Gomes; Paula Costa; Filipe Paradela; Frederico Castelo Ferreira; Nuno Torres Faria; Paula Mugica; Helena M. Pinheiro; Isabel Sá-Correia; Francisco Gírio (Biomass and Bioenergy, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Transfiguration of discarded PVDF ultrafiltration membranes: Optimization of pyrolysis parameters for high-value char production - Isabel Pereira da Silva; Ali Maged; Victoria Pinheiro Lima Abreu; Ana Luisa Quintanilha Candido; Sônia Denise Ferreira Rocha; Eduardo Coutinho de Paula (Waste Management, 2024)

The hide-and-seek effect of pulsed-flows in a potamodromous cyprinid fish - Renan Leite; Maria João Costa; Daniel Mameri; Fernando Afonso; António Pinheiro; José Maria Santos; Isabel Boavida (Hydrobiologia, 2024)
The artificial pulsed-flows impact associated with hydropower production on the downstream biological and physical processes has been extensively addressed, showing that it may cause fish drift while changing fish habitat selection toward lower water velocity patches, acting as refuge areas. We aimed to evaluate the attraction efficiency of two flow-refuges differing in their approaching angles, for Luciobarbus bocagei at an indoor experimental flume. We tested two flow-refuge insertion angles (45° and 70°), and two flow events (base 7 L/s and pulsed-flow 60 L/s) for each. To analyze flow-refuge efficiency, we quantified fish individual and group patterns, flow-refuge use, and permanence time, while measuring glucose and lactate responses. The results showed that the individual frequency of use during simulated pulsed-flow was higher, especially on the 45° flow-refuge. The simulated pulsed-flow condition did not disrupt group behavior for both approaching angles. Glucose and lactate analysis did not trigger physiological responses in the tested trials. The 45° flow-refuge was used more often than the 70°. The narrowing of the channel caused by the 45° flow-refuge, and the consequent higher flow homogeneity increased the attractiveness of the flow-refuge. Therefore, the flow-refuge insertion angle should be a decisive criterion in the construction and installation of flow-refuges for cyprinids, and be considered a potential indirect mitigation measure.

Functional Conception of Biomimetic Artificial Reefs Using Parametric Design and Modular Construction - Dmytro Maslov; Fabio Cruz; Marisa Pinheiro; Tiago Miranda; Isabel Brito Valente; Vasco Ferreira; Eduardo Pereira (Journal of Marine Science and Engineering, 2024)
Artificial reefs featuring different shapes and functions have been deployed around the world, causing impacts on marine ecosystems. However, the approaches typically used to deliver topological complexity, flexibility and expanding requirements to prospective structures during the initial design stages are not well established. The aim of this study was to highlight the advantages and provide evidence on how modularity and parametric design can holistically leverage the performance of multifunctional artificial reefs (MFARs). In particular, the goal was to develop a parametric design for MFAR and establish a direct relationship between specific design parameters and the MFAR target functions or design requirements. The idea of implementing the parametric design for generating the initial biomimetic geometry of the individual modular unit was explored. Furthermore, possible ways of manipulating the geometric parameters of the individual module and the whole assembly were proposed. The findings suggest that, by adopting the developed procedure and the examples studied, several functions may be reached within a single assembly: the promotion of marine biodiversity restoration, the support of scientific platforms with various sensors, as well as the development of recreational diving and of touristic attraction areas. Acquired knowledge suggests that the concept of a nature-like design approach was developed for artificial reefs with varying scales, complexity and functions, which widens the range of possibilities of how smart design of human-made underwater structures may contribute to benefiting the near shore ecosystems.

The study of galactomannans with different molecular weights and their ability to form microparticles suitable for pulmonary delivery - Miguel F. Galrinho; Lisete M. Silva; Guido R. Lopes; Bernardo A.C. Ferreira; Sara A. Valente; Isabel Ferreira; Benedita A. Pinheiro; Angelina S. Palma; Dmitry V. Evtuguin; José A. Lopes da Silva; Margarida Almeida; Paula Ferreira; et al. (Carbohydrate Polymers, 2024)

Gender diversity and climate disclosure: a tcfd perspective - Ana Isabel Dias; Pedro Pinheiro; Sónia Fernandes (Environment, Development and Sustainability, 2024)
The paradigm of corporate environmental disclosures aimed at investors developed in 2017 with the Task Force on Climate-related Financial Disclosures (TCFD) recommendations. Existing literature on social responsibility disclosures points to gender diversity on the board of directors as an influencing factor. This study aims to assess the influence of gender diversity in climate-related financial disclosures, as recommended by the TCFD based on a sample of 27 companies operating within the sectors of electricity, oil, coal and gas, water, and alternative energy that have announced their adherence to the recommendations from 2017 to 2021. By applying a linear regression model, the results indicate the presence of a positive association between the level of TCFD disclosures and board gender diversity, as well as other factors, such as company size, CEO duality, and general liquidity. However, the influence of board gender diversity on corporate reporting based on the TCFD recommendations suggests that the commitment of boards to the reporting of climate change risks and opportunities is not significantly dependent on gender diversity, as the presence of women in the Boards is favorable for the reporting but without a significant impact on the level of disclosures. This research offers insights into sustainability reporting practices, focusing on a relatively new perspective of reporting climate-related financial topics and their determinants. The findings hold implications for organizational leaders and stakeholders, mainly investors, as these recent sustainable reporting practices are challenging but also bring new opportunities related to transparency towards climate-related issues.

Potential effects of the discharge of wastewater treatment plant (WWTP) effluents in benthic communities: evidence from three distinct WWTP systems - Carlos Silva; Joana Isabel Santos; Tânia Vidal; Susana Silva; Salomé Fernandes Pinheiro Almeida; Fernando José Mendes Gonçalves; Nelson Abrantes; Joana Luísa Pereira (Environmental Science and Pollution Research, 2024)
Wastewater treatment plant (WWTP) effluents can be sources of environmental contamination. In this study, we aimed to understand whether effluents of three different WWTPs may have ecological effects in riverine recipient ecosystems. To achieve this, we assessed benthic phytobenthos and macroinvertebrate communities at three different locations relative to the effluent discharge: immediately upstream, immediately downstream and 500-m downstream the effluent discharge. Two approaches were employed: the ecological status classification as defined in the Water Framework Directive (WFD) based on biological indicators; constrained multivariate analysis to disentangle the environmental drivers (physicochemical variables and contaminants, namely metals, polycyclic aromatic hydrocarbons, pharmaceuticals, and personal care products) of ecological changes across the study sites. The results showed inconsistencies between the WFD approach and the multivariate approach, as well as between the responses of macroinvertebrates and diatoms. The WWTP effluents impacted benthic communities in a single case: macroinvertebrates were negatively affected by one of the WWTP effluents, likely by the transported pharmaceuticals (other stressors are essentially homogeneous among sites). Given the findings and the scarcity of consistent evidence on ecological impacts that WWTP effluents may have in recipient ecosystems, further research is needed towards more sustainable regulation and linked environmental protection measures.

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

13C labelling reveals details of the soybean (Glycine max (L.) Merrill) seedling metabolic network - Janderson Moraes de Lima; Vitoria Pinheiro Balestrini; Isabel Caroline Gomes Giannecchini; Guilherme Henrique Moss Barreto Cor de Oliveira; Thomas Christopher Rhys Williams (Theoretical and Experimental Plant Physiology, 2024)

Intermediary floral traits between natural hybrid and its parents in the Xiquexique (Cactaceae) - Sinzinando Albuquerque-Lima; Paulo Milet-Pinheiro; Daniela M. A. F. Navarro; Nigel P. Taylor; Daniela C. Zappi; Isabel C. Machado (Organisms Diversity & Evolution, 2024)

First report of phenolic compounds isolated from Inga stipularis DC. (fabaceae) leaves - Anderson de Santana Botelho; Wandson Braamcamp de Souza Pinheiro; José Rodrigues Pinheiro Neto; Sonia das Graças Santa Rosa Pamplona; Kyouk Isabel Portilho dos Santos; Milton Nascimento da Silva; Mara Silvia Pinheiro Arruda (Natural Product Research, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

Staminode of Jacaranda rugosa A.H. Gentry (Bignoniaceae) promotes functional specialization by ensuring signaling and mechanical fit to medium-sized bees - Cristina Adriane de Souza Pontes; Arthur Domingos-Melo; Paulo Milet-Pinheiro; Daniela Maria do Amaral Ferraz Navarro; Tarcila Lima Nadia; Isabel Cristina Machado (Organisms Diversity & Evolution, 2022)

Negative impacts of dominance on bee communities: Does the influence of invasive honey bees differ from native bees? - Lucas A. Garibaldi; Néstor Pérez‐Méndez; Guaraci D. Cordeiro; Alice Hughes; Michael Orr; Isabel Alves‐dos‐Santos; Breno M. Freitas; Favízia Freitas de Oliveira; Gretchen LeBuhn; Ignasi Bartomeus; Marcelo A. Aizen; Patricia B. Andrade; et al. (Ecology, 2021)
Invasive species can reach high abundances and dominate native environments. One of the most impressive examples of ecological invasions is the spread of the African subspecies of the honey bee throughout the Americas, starting from its introduction in a single locality in Brazil. The invasive honey bee is expected to more negatively impact bee community abundance and diversity than native dominant species, but this has not been tested previously. We developed a comprehensive and systematic bee sampling scheme, using a protocol deploying 11,520 pan traps across regions and crops for three years in Brazil. We found that invasive honey bees are now the single most dominant bee species. Such dominance has not only negative consequences for abundance and species richness of native bees but also for overall bee abundance (i.e., strong “numerical” effects of honey bees). Contrary to expectations, honey bees did not have stronger negative impacts than other native bees achieving similar levels of dominance (i.e., lack of negative “identity” effects of honey bees). These effects were markedly consistent across crop species, seasons and years, and were independent from land‐use effects. Dominance could be a proxy of bee community degradation and more generally of the severity of ecological invasions.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

It's raining fragrant nectar in the Caatinga: evidence of nectar olfactory signaling in bat‐pollinated flowers - Arthur Domingos‐Melo; Paulo Milet‐Pinheiro; Daniela Maria do Amaral Ferraz Navarro; Ariadna Valentina Lopes; Isabel Cristina Machado (Ecology, 2020)

Subtle Chemical Variations with Strong Ecological Significance: Stereoselective Responses of Male Orchid Bees to Stereoisomers of Carvone Epoxide - Katharina Brandt; Stefan Dötterl; Roman Fuchs; Daniela Maria do Amaral Ferraz Navarro; Isabel Cristina Sobreira Machado; Daniel Dobler; Oliver Reiser; Manfred Ayasse; Paulo Milet-Pinheiro (Journal of Chemical Ecology, 2019)

Flowers as sleeping places for male bees: somehow the males know which flowers their females prefer - Mardiore Pinheiro; Isabel Alves-dos-Santos; Marlies Sazima (Arthropod-Plant Interactions, 2017)

Performance of Lynch syndrome predictive models in quantifying the likelihood of germline mutations in patients with abnormal MLH1 immunoexpression - Verónica Cabreira; Carla Pinto; Manuela Pinheiro; Paula Lopes; Ana Peixoto; Catarina Santos; Isabel Veiga; Patrícia Rocha; Pedro Pinto; Rui Henrique; Manuel R. Teixeira (Familial Cancer, 2017)

Assessing foraging strategies of herbivores in Mediterranean oak woodlands: a review of key issues and selected methodologies - Maria Isabel Ferraz de Oliveira; Elsa Lamy; Miguel N. Bugalho; Margarida Vaz; Cristina Pinheiro; Manuel Cancela d’Abreu; Fernando Capela e Silva; Elvira Sales-Baptista (Agroforestry Systems, 2013)

Sequencing of modern Lepus VDJ genes shows that the usage of VHn genes has been retained in both Oryctolagus and Lepus that diverged 12 million years ago - Ana Pinheiro; Isabel G. Fernández de Mera; Paulo C. Alves; Christian Gortázar; José de la Fuente; Pedro J. Esteves (Immunogenetics, 2013)

Stroop matching task: role of feature selection and temporal modulation - Isabel A. David; Eliane Volchan; Jaime Vila; Andreas Keil; Letícia de Oliveira; Aydamari J. P. Faria-Júnior; Pandelis Perakakis; Elisa C. Dias; Izabela Mocaiber; Mirtes G. Pereira; Walter Machado-Pinheiro (Experimental Brain Research, 2011)

TP53 germline mutations in Portugal and genetic modifiers of age at cancer onset - Carla Pinto; Isabel Veiga; Manuela Pinheiro; Ana Peixoto; Armando Pinto; José M. Lopes; Rui M. Reis; Carla Oliveira; Manuela Baptista; Lúcia Roque; Fernando Regateiro; Luís Cirnes; et al. (Familial Cancer, 2009)

Smoking and gastric cancer: systematic review and meta-analysis of cohort studies - Ricardo Ladeiras-Lopes; Alexandre Kirchhofer Pereira; Amanda Nogueira; Tiago Pinheiro-Torres; Isabel Pinto; Ricardo Santos-Pereira; Nuno Lunet (Cancer Causes & Control, 2008)

Physiological behaviour of Saccharomyces cerevisiaeunder increased air and oxygen pressures - Rita Pinheiro; Isabel Belo; Manuel Mota (Biotechnology Letters, 1997)